Insegurança hídrica: medidas adaptativas autônomas usadas pela população na cidade de Belém, Pará - RODRIGUES, Tayná Cristiny Nunes Flexa (Universidade Federal do Pará, 2023)
The Amazon region, where the capital of the state of Pará, Belém, is located, has a large availability of water resources and constant rainfall well distributed throughout the year. However, there are frequent occurrences of interruptions in the water supply. Part of the population has no access to water in their homes or the supply is irregular, despite the fact that Belém does not present meteorological or hydrological droughts. Because of the interruptions in the water supply, the population needs to seek autonomous adaptive measures, without help from the government or private institutions, to acquire water, since the aforementioned element is essential in daily life. The research aims to identify the autonomous adaptive measures adopted by the population of Belém to reduce the inconvenience associated with the lack of water, called water insecurity. Therefore, it was analyzed in online and television newspapers - in the period from 2014 to 2020 - the frequency in which neighborhoods were notified, the causes of the interruption, the consequences, as well as the decisions taken by residents to obtain water. From the journalistic data, the water insecurity index of Belém's neighborhoods was identified, dividing them into three categories: high, medium and low. The results obtained correspond both to the production of the water insecurity index map per neighborhood, as well as the information about the time, causes and consequences arising from the interruption in water supply, besides identifying the autonomous adaptive measures used by the population, such as: buying mineral water, collecting rainwater and using well water, generally considered as reactive measures, since they occur either at the time or after the lack of water. Thus, we highlight the need for improvements in the infrastructure of the water supply system, to obtain a regular and quality supply, because water is everyone's right and essential for the well-being of the population.